1999
DOI: 10.1074/jbc.274.36.25205
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning of a Novel Androgen Receptor Subtype

Abstract: There has been general acceptance that only one type of androgen receptor (AR) exists in an individual. This contrasts with other members of the nuclear receptor superfamily where multiple forms have been reported (e.g. estrogen receptor ␣/␤, thyroid hormone receptor ␣/␤, etc.). We have previously identified 11-ketotestosterone (a potent androgen in teleosts) as the spermatogenesis-inducing hormone of the Japanese eel and have cloned its receptor (eAR1) cDNA from eel testis. Here we report on the cloning of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(73 citation statements)
references
References 22 publications
5
68
0
Order By: Relevance
“…In fish, artificial hormones have been reported to affect various organs like kidney, liver, muscle, testes and ovary (Ikeuchi et al 1999). Other experiments revealed that females grow faster than males because spermatogenesis occurs much faster than oogenesis during gonadotropin treatment (Ohta et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In fish, artificial hormones have been reported to affect various organs like kidney, liver, muscle, testes and ovary (Ikeuchi et al 1999). Other experiments revealed that females grow faster than males because spermatogenesis occurs much faster than oogenesis during gonadotropin treatment (Ohta et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally accepted that, instead of DHT, 11-ketotestosterone is biologically the most important androgen in teleosts (Kime 1993), which was supported by the findings of Miura et al (1991) that 11-ketotestosterone by itself induced complete spermatogenesis in the Japanese eel. DHT has been detected in several teleost species (Kime 1993) and teleost androgen receptors may sometimes display an affinity to 5 -reduced androgens similar to or even greater than to 11-oxygenated androgens (Ikeuchi et al 1999, Sperry & Thomas 2000, Braun & Thomas 2004. In the case of zebrafish, there are no data available on the true molecular character of the biologically active androgens and the androgen receptor itself has not been characterized so far.…”
Section: Enzymatic Properties Of Human and Zebrafish 17 -Hsdmentioning
confidence: 99%
“…In contrast to mammals, especially the molecular mechanisms underlying androgen function in fish are still widely unknown. The androgen receptors from several different fish species have been cloned and characterized at the molecular level (Ikeuchi et al 1999, Sperry & Thomas 1999, Takeo & Yamashita 1999, Touhata et al 1999, Kim et al 2002, Wilson et al 2004 and central enzymes of the general pathway leading to the formation of steroid hormones, for example P450 cholesterol side-chain cleavage enzyme (Lai et al 1998, Hsu et al 2002 and 17 -hydroxylase/17,20-lyase (Sakai et al 1992, Trant 1995, Kazeto et al 2000b, have been identified as well. Concerning enzymes of the 17 -HSD family though, only 17 -HSD type 1 from eel (Kazeto et al 2000a) and zebrafish (Mindnich et al 2004) have been studied in detail and in both species the enzyme does not seem to be involved in androgen metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its phenotypic sex can easily be manipulated by hormonal treatment [9]. Teleosts, including medaka, have three paralogous genes for ER-esr1 (or ERa), esr2a (or ERb1) and esr2b (or ERb2)-and two genes for AR-ara (or ARa) and arb (or ARb), which arose from the whole genome duplication early in teleost evolution [10,11]. Here, we assessed the expression of these genes in the medaka brain and found that several brain nuclei express both ER and AR almost exclusively only in females, representing female-specific target sites for both oestrogen and androgen.…”
Section: Introductionmentioning
confidence: 99%